Assessment of glycemic gap as a biomarker of severity and outcome of pulmonary embolism in diabetic patients - Eman Shebl (Egyptian Journal of Chest Disease and Tuberculosis, 2018)
Objective The aim was to assess the role of glycemic gap as a biomarker of pulmonary embolism severity and outcome in diabetic patients. Patients Diabetic patients who were 18 years of age or older admitted with confirmed diagnosis of pulmonary embolism (n=280) were included in the study. Methods On admission, blood glucose level was measured. HbA1c was measured. To convert HbA1c levels to the estimated long-term average glucose levels (eAG) for the previous 3 months, the equation AG = 28.7×HbA1c-46.7 was used. From the glucose level at ED admission minus the eAG, the glycemic gap was calculated. The severity of pulmonary embolism was assessed by the pulmonary embolism severity index (PESI). Results There was a significant positive correlation between glycemic gap and the severity of pulmonary embolism and length of hospital stay. There was a significant difference of the glycemic gap between nonsurvivors and survivors (110.3±35.6 vs.48.8±31.3; P< 0.001), patients with and without clinical deterioration (108±34.1 vs. 48.1±31.1; P< 0.001), and patients who needed ICU admission and those who did not need ICU admission (107.3±31.9 vs. 46.2±29.7; P< 0.05). At a cut-off value of glycemic gap of greater than or equal to 79, sensitivity, specificity, positive predictive value, and negative predictive value were 100, 82, 23, and 100%, respectively. Multivariate logistic regression of potential predictors of mortality identified two independent predictors: PESI (P<0.001) and glycemic gap (P=0.042). Conclusion Elevated glycemic gap between serum glucose levels upon admission and the HbA1c-derived average glucose was associated with increased severity and mortality in diabetic patients with pulmonary embolism.